Evaluación de un Sistema de Gestión de la Calidad ISO 9001 para orientarlo a la satisfacción del cliente e innovación de servicios educativos en instituciones educativas de básica y media (2016)
The organizations have chosen to implement quality management systems (QMS), and year after year have increased considerably in all sectors of the industry. Similarly, educational institutions have chosen to incorporate the international model ISO 9001, to support their academic activities and presented some issues regarding their integration or adaptation for proper implementation, some of these disadvantages even from implementing QMS by hiring consulting firms. It is evident that there are gaps not only in literature in relation to the contributions of a QMS to educational institutions in terms of innovation, but they do not address case studies, which is why this research deals with case studies and analysis corresponding to provide an input not only to organizations that intend to adopt innovation - oriented, but future research a QMS. That is why through this research, we want to know the contribution that could have the SGC to innovation and customer satisfaction for the purpose of responding to such linking and integrating quality practices in the school and innovation. Finding the best way is to address the QMS to guide you to results focused on the satisfaction of stakeholders, results that can be achieved by incorporating key process activities (including activities that warrant greater commitment of resources), participation staff and training. Given the satisfaction of stakeholders is recognized as innovation and its approach to QMS it is given.